2012
DOI: 10.1093/rfs/hhs117
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Value Creation: Evidence from Private Equity

Abstract: We examine deal-level data from 395 private equity transactions in Western Europe initiated by large private equity houses during the period 1991 to 2007. We un-lever the deallevel equity return and adjust for un-levered return to quoted peers to extract a measure of abnormal performance of the deal. The abnormal performance is significantly positive on average, and stays positive in periods with low sector returns. In the cross-section of deals, higher abnormal performance is related to greater growth in sale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(69 citation statements)
references
References 39 publications
(35 reference statements)
8
61
0
Order By: Relevance
“…There is no significant difference between the board meeting frequency of MBO companies and the population. The frequency of board meetings in Chinese MBOs appears to be less than in Western buyouts which hold an average of 12 formal meetings per year (Acharya and Kehoe, 2008). …”
Section: The Frequency Of Board Meetingsmentioning
confidence: 87%
See 1 more Smart Citation
“…There is no significant difference between the board meeting frequency of MBO companies and the population. The frequency of board meetings in Chinese MBOs appears to be less than in Western buyouts which hold an average of 12 formal meetings per year (Acharya and Kehoe, 2008). …”
Section: The Frequency Of Board Meetingsmentioning
confidence: 87%
“…Investors in Western buyouts tend to be more active than in listed corporations, one manifestation of which is more frequent board meetings (Acharya and Kehoe, 2008). The composition and functioning of boards of public-to-private buyout transactions may not be homogeneous but vary according to whether the buyout was aimed at improving efficiencies or exploiting growth opportunities (Wright et al, 2000.…”
Section: The Role Of the Board In Buyoutsmentioning
confidence: 99%
“…Bajramovic (2016) shows that in transition economies ownership structure highly correlates with capital structure employed by companies. Acharya et al (2013) indicate that unproportionally larger portion of private equity transactions are successful when factoring in financial leverage and sector returns. Higher rate of success is related to better sales and operating margins compared to that of public companies.…”
Section: Ownership Structurementioning
confidence: 99%
“…Until Fang and Leeds, 2008a, b). The international literature shows that active private equity ownership improves managerial behavior and accountability (Acharya et al, 2009;Kaplan and Stromberg, 2009, p. 131). Private equity owners are also more active in operational engineering -initiating operational and strategic change such as value creation plans, acquisitions, divestitures, strategic repositioning, new product development, and so forth (Acharya et al, 2009;Bernstein et al, 2009;Nikoskelainen and Wright, 2007).…”
Section: Governance and Operation Change Statisticsmentioning
confidence: 99%
“…LBO owners (typically) are active in corporate governance and are able to make management changes because they have majority equity ownership and the majority of board seats. Acharya et al (2009) studied private equity transactions in the UK between 1996 and 2004, and found that one third of CEOs are replaced in the first 100 days of an LBO, and two-thirds are replaced at some point over a 4-year period. Table V reports managerial change in Asian LBOs in our data.…”
mentioning
confidence: 99%